Water Quality I ndex of 11 Streams Pouring into Um-Alnaaj Marsh - Alsaad, Mohammed (Nahrain University College of Engineering Journal, 2014)
This paper assesses the water qualityindex of 11 streams (rivers) and thereceiving UM- AL NAAJ marshland atMisan governorate and how the waterquality is improved when entered themarshland. The assessment employ theCanadian Council of Ministers of theEnvironment Water Quality Index (CCMEWQI) which incorporates three elements:Scope (F 1)- the number of water qualityparameters not meeting water qualityobjectives; Frequency (F 2)- the number oftimes the objectives are not met; andAmplitude (F 3)- the extent to which theobjectives are not met. The index produces anumber between 0 (worst) to 100 (best) toreflect the water quality. Iraqi guidelines fordrinking water and the site-specificmeasured values of 5 variables are used inthe index calculation.Variables included inthe index calculation were, watertemperature, dissolved oxygen, totaldissolved solids, pH, turbidity. The CCMEWQI analysis show that the average waterquality of the 11 streams, feeding Um-Alnaaj marshland is rated as fair based on2010 data, meaning that the conditions ofthe streams were sometimes depart fromnatural or desirable levels while the qualityof water inside the marsh was ranging fromgood to excellent.